Analisis Kontrastif Maf’ûl Ma’ah Terhadap Penerjemahan Bahasa Inggris dan Implikasinya Dalam Pembelajaran Translation and Interpretation - Ikhwan Tirmizi; Wirawan Jamhuri; Sahabi Alif Suhartami (Institut Agama Islam Negeri Metro, 2021)
This research was conducted to facilitate the translation of maf'ul ma'ah into English because basically the translation of maf'ul ma'ah is difficult because the wawu used does not only have one meaning while there is no standard term in English to make it easier.Furthermore, the purpose of this research is firstly to explain the similarities and differences between maf'ul ma'ah in Arabic and the accompaniment complement in English, secondly to describe the forms of translation of maf'ûl ma'ah into English, thirdly to find out the implications of the analysismaf'ûl ma'ah contrastive to English translation.Researchers have classified examples of translating maf'ul ma'ah into English and have also been described in this study so that it can be seen that the translation of wawu ma'iyah into English does not only use one word but there are 7 clear meanings along with how the meaning contained therein. So from the results of the analysis that has been done, in general it can be concluded that wawu ma'iyah is translated based on the context of the sentence. Kata Kunci: Contrastive Analysis, Maf’ulMaah, Translation and Interpretation